2011
DOI: 10.1097/sla.0b013e31822b8b2f
|View full text |Cite
|
Sign up to set email alerts
|

Superior Preservation of DCD Livers With Continuous Normothermic Perfusion

Abstract: Although 60 minutes recuperative NECMO is better than CS alone, NMP improves further on NECMO and may have a role in preserving DCD livers in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 37 publications
4
136
0
Order By: Relevance
“…These findings are important for several reasons. First, NMP is rapidly becoming the subject of preclinical and clinical research (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Second, different research groups have used various perfusion protocols but none have compared their efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are important for several reasons. First, NMP is rapidly becoming the subject of preclinical and clinical research (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Second, different research groups have used various perfusion protocols but none have compared their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Normothermic machine perfusion (NMP) is a preservation technology with potential to prevent both ischemic injury and the deleterious effect of cold temperatures by perfusing organs with a warm oxygenated perfusion solution. Numerous studies have demonstrated the advantage of NMP over CS in the preservation of DCD livers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), suggesting that NMP may greatly benefit the practice of liver transplantation. conducted using whole blood (WB) (9)(10)(11)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Innovative approaches for lowering the biliary mobidity of DCD-LT include thrombolytic agents (83) or machine perfusion (84). First clinical results using backtable injection of tissue plasminogen activator (TPA) into the donor hepatic artery before DCD-LT revealed a low incidence of ischemic cholangiopathy of 9% and an overall biliary complication rate of 27%.…”
Section: Special Issues Of Dcdmentioning
confidence: 99%
“…Research into machine perfusion systems (including in situ and ex situ) is consequently an active field in donor organ recovery and preservation. [45][46][47][48] In 51,52 Compared with ex situ machine perfusion, in situ perfusion is preferable because it obviates the need for exhaustive techniques to reconnect the organs to the machine, increasing simplicity. Additionally, it is an indis-pensable technique that can provide the opportunity to meet legal and logistic requirements for organ recovery without excessive WIT, and depending on the legal opportunities, it can be initiated prior to obtaining consent for organ donation.…”
Section: Liver Preservation Techniquesmentioning
confidence: 99%